2019
DOI: 10.21608/ejchem.2019.2868.1804
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of the functional properties of polyester microfiber single jersey using some nano-materials

Abstract: I N this study knitted single jersey samples by polyester microfiber (150/288) yarn count were manufactured. Three different machines gauge (20-24-28) was performed. The polyester knitted fabrics were treated with nano clay and nano silica with two concentrations (1.5% & 3%). The samples specifications as stitch length, stitch density and tightness factor were measured while weight, thickness, bursting, UPF, air permeability and stiffness properties were tested. The treated polyester samples dyed with dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The fastness properties of coloured wool and polyamide 6 fabrics were further evaluated and reported in Tables (7)(8)(9)(10). In all treatment conditions, the siO2 NPs incorporated both fabrics showed fastness results ranged from well to very well when using conventional heating and from very well to excellent when using microwave irradiation which is referred to the chemically stable of siO 2 NPs on the fabrics and it follows the following order: Basic dyes > Acid Dyes > Direct dyes, Polyamide 6 > wool fabric, Microwave irradiation > traditional heating.…”
Section: Colour Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fastness properties of coloured wool and polyamide 6 fabrics were further evaluated and reported in Tables (7)(8)(9)(10). In all treatment conditions, the siO2 NPs incorporated both fabrics showed fastness results ranged from well to very well when using conventional heating and from very well to excellent when using microwave irradiation which is referred to the chemically stable of siO 2 NPs on the fabrics and it follows the following order: Basic dyes > Acid Dyes > Direct dyes, Polyamide 6 > wool fabric, Microwave irradiation > traditional heating.…”
Section: Colour Measurementsmentioning
confidence: 99%
“…Also, polyamide fabrics treated with tannic acid to improve the dyeability of polyamide towards cationic dyes as well as fastness properties using different conditions [4]. Nano silicon dioxide was applied in textile industry to incorporate multifunctional properties such as increase the tensile strength, tear strength, antipilling, UPF protection and antimicrobial activity of viscose, polyester, nylon and wool fibres [5][6][7][8] . Liu et al studied the preparation and characterization of PET/silica or polyamide/ silica nano composites and they found that the purchased organic modified silica was dispersed in ethylene glycol by sonication at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Tarek Elsayed et al suggested the use of aramid, carbon and glass fibres via pultrusion to produce local rebars [14]. Knitting techniques usually give fabrics unique performance characteristics due to their yarnloop ing shape [15,16]. Those types of knitted fabrics have been employed as textile reinforced concrete (TRC) for concrete reinforcement in some stud ies [17].…”
Section: Introductionmentioning
confidence: 99%
“…Fabric stiffness is wanted to be reduced for a good drape in many apparel fabrics, and to optimize the sewing parameters such as stitch density, sewing thread type and size, and seam allowance in order to control the stiffness of the fabric on the garment [16,17]. Seam slippage is one of the most important properties of seam especially in silk fabrics and it is a ratio between seam strength and fabric strength.…”
Section: Introductionmentioning
confidence: 99%